Effect of bosentan in pulmonary hypertension development in systemic sclerosis patients with digital ulcers. - Ivan Castellví; Carmen Pilar Simeón; Monica Sarmiento; Jordi Casademont; Hèctor Corominas; Vicenç Fonollosa (PLoS ONE, 2020)
Systemic sclerosis is a disease where microcirculation damage is critical in their beginning and vascular complications have similar pathogenic findings. Digital ulcers are a frequent complication in systemic sclerosis patients and pulmonary hypertension is one of the leading causes of death. The use of bosentan has been shown to be useful for the treatment of pulmonary arterial hypertension and to prevent new digital ulcers. However, is unknown if bosentan can prevent pulmonary hypertension. Our objective was to determine if bosentan is useful to prevent pulmonary hypertension in SSc patients. A retrospective study in 237 systemic sclerosis patients with digital ulcers history treated or not with bosentan to prevent it was made. We analyzed the occurrence of pulmonary hypertension defined by an echocardiogram pulmonary arterial pressure > 40 mmHg in the entire cohort. Demographic, clinical, and treatment variables were recorded for all patients. Statistical significance was denoted by p values < 0.05. Fifty-nine patients were treated with bosentan a median of 34 months. 13.8% of treated patients had pulmonary hypertension vs 23.7% of untreated patients (p 0.13) during the follow up. In multivariate analysis patients not treated with bosentan had 3.9fold-increased risk of pulmonary hypertension compared with patients under bosentan treatment (p < 0.02). Moreover the percentage carbon monoxide diffusing capacity (DLCO) in bosentan treated patients did not decrease from baseline to the end of follow-up (61.8±14% vs 57±20.1%, p = 0.89). We concluded that Systemic sclerosis patients with digital ulcers treated with bosentan seems to have less risk to develop pulmonary hypertension and to stabilize DLCO.